MO023SARCOPENIA, CHRONIC KIDNEY DISEASE AND RISK OF MORTALITY: FINDINGS FROM 426, 839 INDIVIDUALS IN THE UK BIOBANK. (6th June 2020) - Wilkinson, Thomas; Miksza, Joanne; Baker, Luke; Lightfoot, Courtney; Watson, Emma; Yates, Thomas; Smith, Alice
Abstract: Background and Aims: Sarcopenia describes a degenerative and generalised skeletal muscle disorder involving the loss of muscle mass and function. In studies of the general population, sarcopenia is associated with adverse outcomes including falls, functional decline, frailty, and mortality. However it remains an under-recognised yet important clinical problem in an ever-increasing ageing and multimorbid renal population. Whilst sarcopenia has been widely studied in end-stage renal disease, there is limited evidence of its prevalence and effects in those not requiring dialysis, particularly in large cohort studies and using the latest sarcopenia definitions. Using the UK Biobank, we aimed to identify the prevalence of sarcopenia in individuals with non-dialysis CKD and its association with mortality. Method: 426, 839 participants were categorised into a CKD (defined as eGFR <60ml/min/1.73m 2 not requiring dialysis) and a non-CKD comparative group (no evidence of CKD). Sarcopenia was diagnosed using criteria from the EWGSOP2: 'probable sarcopenia' (low handgrip strength (HGS) <27 and 16kg, males and females respectively); 'confirmed sarcopenia' (low HGS plus low muscle mass, appendicular lean mass <7.0 and 5.5 kg/m 2 as measured by bioelectrical impedance); and 'severe sarcopenia' (low HGS and muscle mass plus slow gait speed). Patients requiring existing renal replacement therapy were excluded. All-cause mortality was extracted from data linkage to national death records with a median follow up of 9.0 years. Data were analysed using Cox survival models. Results: CKD (non-dialysis dependent) was identified in n=7, 623 individuals (mean age 62.7 (±5.9) years, 44% male, eGFR 52.5 (±7.7) ml/min/1.73m 2 ) compared to n=419, 216 in the non-CKD comparative group (mean age 56.1 (±8.1) years, 47% male). 'Probable sarcopenia' was identified in 9% of individuals with CKD compared to 5% in those without CKD (P<0.001). 'Confirmed sarcopenia' was observed in 0.3% of those with CKD (vs. 0.2% in the non-CKD group, P<0.001). 0.2% of CKD patients satisfied all three criteria ('severe sarcopenia') compared to 0.03% in those without CKD (P<0.001). In CKD, sarcopenia was significantly associated with all-cause mortality: 'probable sarcopenia', unadjusted hazard ratio (HR) 1.95 (95%CI 1.57 to 2.42), P<0.001 (Figure 1); 'confirmed sarcopenia', HR 5.1 (2.5 to 10.3) P<0.001; 'severe sarcopenia', HR 5.1 (1.9 to 13.5) P=0.001. Conclusion: In the largest cohort of its kind, probable sarcopenia was present in 9% of individuals with non-dialysis CKD. The risk of sarcopenia was significantly higher in those with CKD than those without. Regardless of criteria used, CKD patients with sarcopenia were approximately 2-5 times more likely to die than those without sarcopenia. Worryingly, the risk of sarcopenia was elevated even in patients with early stage mild to moderate CKD. Our results show that sarcopenia, including just the presence of low muscle strength, is an important predictor of mortality in early non-dialysis CKD. Measuring sarcopenia as standard practice may identify those most at risk of future adverse events and in need of appropriate interventions to mitigate its negative effects.